Pencarian Identitas Aliran Kebatinan di Indonesia - Naila Ananda Risa; Kheria Yulia Ningrum (HK-Publishing, 2023)
AbsractIndonesia is a country with a multicultural society that forms a heterogeneous society, including in terms of religious diversity. With regard to religion, Indonesia officially establishes six religions as official religions and is recognized by the state, these religions namely Islam, Protestant Christianity, Catholic Christianity, Hinduism, Buddhism and Confucianism. However, with the cultural diversity that is owned by the people of Indonesia there are other religions that exist outside of the six official religions. Among the many other religions outside the six official religions recognized by the state, one of them is the Mysticism School. Many of the kebatinan schools are considered part of Indonesian tradition and culture. Apart from that, Kebatinan is also considered as a habit and philosophy of life that is approved by its adherents. It is known that even though they adhere to one of the official religions, there are also people who still practice and agree with the customs taught in the Kebatinan school, thus showing that this kebatinan school is still embedded in the daily lives of Indonesian people even though it is not made as the main religion and is only carried out as a philosophy of life. . On the other hand, for adherents of the Kebatinan sect, the Kebatinan sect is considered a genuine religious sect originating from Indonesia even before the presence of other major religions which are widely embraced by the people of Indonesia. Meanwhile, other major religions are imported religions from other countries. The sect of kebatinan itself is one of the religions or beliefs that are adhered to by the people of Indonesia, especially said to be the most widely adhered to by the Javanese people. Nonetheless, in multicultural life in Indonesia, local religions such as kebatinan still experience discrimination from the government, including the non-recognition of local religions or beliefs as a separate entity that is outside religion.Keywords: Identity Politics, Mysticism, Local Religion AbstrakIndonesia merupakan negara dengan masyarakat yang multikultral yang membentuk masyarakat heterogen termasuk dalam hal keberagaman agama. Berkaitan dengan agama, Indonesia secara resmi menetapkan enam agama sebagai agama resmi dan diakui oleh negara, agama-agama tersebut yakni agama Islam, Kristen Protestan, Kristen Katolik, Hindu, Buddha, dan Konghucu. Namun, dengan keberagaman budaya yang dimiliki oleh masyarakat Indonesia terdapat agama-agama lain yang hadir diluar keenam agama resmi tersebut. Diantara banyaknya agama lain diluar enam agama resmi yang diakui negara, salah satunya terdapat Aliran Kebatinan. Aliran kebatinan sendiri banyak dianggap sebagai bagian dari tradisi dan kebudayaan Indonesia. Selain itu, aliran Kebatinan juga dianggap sebagai kebiasaan dan filosofi hidup yang diamini oleh penganutnya. Diketahui meskipun menganut salah satu agama resmi, terdapat juga masyarakat yang masih menjalankan dan mengamini kebiasaan yang diajarkan dalam aliran Kebatinan, sehingga menunjukkan bahwa aliran kebatinan ini masih lekat dalam kehidupan masyarakat Indonesia sehari-hari meskipun bukan dijadikan sebagai agama utama dan hanya dijalankan sebagai filosofi hidup. Disisi lain, bagi penganut aliran Kebatinan, aliran Kebatinan dianggap sebagai aliran agama asli yang berasal dari Indonesia bahkan sebelum hadirnya agama-agama besar lain yang banyak dianut oleh masyarakat Indonesia. Sedangkan agama besar lainnya merupakan agama impor dari negeri lain. Aliran kebatinan sendiri merupakan salah satu agama atau kepercayaan yang dianut oleh masyarakat Indonesia, terutama dikatakan paling banyak dianut oleh masyarakat Jawa. Meskipun demikian, dalam kehidupan multicultural yang ada di Indonesia agama lokal seperti aliran kebatinan masih mengalami diskriminasi dari pemerintah diantaranya dengan belum diakuinya agama-agama atau kepercayaan lokal sebagai suatu entitas tersendiri yang berada di luar agama.Kata kunci: Politik Identitas, Aliran Kebatinan, Agama Lokal